Drivers of Negative Brand Perception in Gauteng - Minnaar, George Frederick (The IIE, 2022)
This study focusses on the negative form of brand perception and the drivers that motivate such feelings in consumers. A 2009 study by Lee, Motion, & Conroy identified the three main motives for a consumer to avoid a brand, namely experiential avoidance (when there is an incongruence between a consumer’s expectations and the actual brand experience), identity avoidance (when there is a discrepancy between the consumer’s personal identity and the image portrayed by the brand) and moral avoidance (when there is an incongruence between the consumer’s moral beliefs and the values portrayed by the brand). The findings of that study have been used to develop a conceptual framework that helps to clarify why consumers avoid some brands. This research paper tests the findings of Lee et al. (2009) against a South African test group to measure whether these same brand avoidance motives are applicable to a local audience, as well as dealing with the implications of such findings.
Keywords: Consumer behaviour; Brand hate; Brand experience; Anti-consumption; Brand avoidance